(untitled) - Cass, Kiera (New York, NY, 2014)
"As her Selection approaches its finish, America must decide where her heart truly lies--and Prince Maxon must pick one winner to wear the crown"--
Keywords: Fiction; Love; Fiction; Princes; Fiction; Social classes; Fiction; Contests; Fiction; Juvenile fiction; Love stories; Princes; Juvenile fiction; Social classes; Juvenile fiction; Contests; Juvenile fiction; Marriage; Marriage; Romance